Isolation of lupeol acetate from fruit peels of Artocarpus camansi - Rosnani Nasution; Nurul Muhabbah; Hira Helwati; Muhammad Bahi; Marianne Marianne; Ulil Amna (Wolters Kluwer Medknow Publications, 2020)
The purpose of this research is to find a lupeol acetate from Artocarpus camansi fruit peel. Ethyl acetate extract of A. camansi fruit peel was obtained by maceration process. After the process of fractionation, it results 3 subfractions (A, B, and C). The subfraction B was rechromatographed and yielded B22pure isolate. Based on data from proton nuclear magnetic resonance, Fourier transform-infrared, and mass spectrometry (MS from gas chromatography-MS), the B22isolate was suspected as lupeol acetate compound (in this study, the presence of lupeol acetate in the A. camansi fruit peel has been reported for the first time).